2023
DOI: 10.20529/ijme.2022.071
|View full text |Cite
|
Sign up to set email alerts
|

Internship: A time to prioritise

Abstract: Medical internship is a yearlong experience that is physically, mentally, and emotionally exhausting. After five years as students, the interns finally get close to achieving what they have always dreamt of. Most of the fundamental clinical knowledge and skills that a student learns are acquired during their internship. For the first time, students gain financial freedom, recognise the importance of a white coat, and are recognised as doctors. Internship helps a student to realise the mechanics of how a hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Among Sirtuins, SIRT3 is the main mitochondrial deacetylase and plays an important role in the maintenance of mitochondrial homeostasis as a stress response protein. SIRT3 increases FOXO3A DNA-binding activity as well as FOXO3A-dependent gene expression [29], which leads to increased respiration to sustain energy metabolism, transactivates SOD and other antioxidant enzymes [30], and activates the transcription of mitophagy genes [24,31,32]. Our results revealed a significant decline of FOXO3A protein expression with the aging of APOE4 mice, implying an influence on mitochondrial oxidative stress in these mice.…”
Section: Discussionmentioning
confidence: 54%
“…Among Sirtuins, SIRT3 is the main mitochondrial deacetylase and plays an important role in the maintenance of mitochondrial homeostasis as a stress response protein. SIRT3 increases FOXO3A DNA-binding activity as well as FOXO3A-dependent gene expression [29], which leads to increased respiration to sustain energy metabolism, transactivates SOD and other antioxidant enzymes [30], and activates the transcription of mitophagy genes [24,31,32]. Our results revealed a significant decline of FOXO3A protein expression with the aging of APOE4 mice, implying an influence on mitochondrial oxidative stress in these mice.…”
Section: Discussionmentioning
confidence: 54%
“…As a main sirtuin located in mitochondria, SIRT3 involves in mitochondrial fatty acid oxidation, mitochondrial biogenesis, and oxidative phosphorylation in skeletal muscle. 40,41 Previous study indicated that the activation of SIRT3 could ameliorate muscle injury via promoting mitochondrial biogenesis. 42 In addition, overexpression of SIRT3 showed higher energy expenditure and lower incidence of muscle atrophy, which was achieved by activating the downstream PPARδ and AMPK.…”
Section: Discussionmentioning
confidence: 65%
“…SIRT3, a nicotinamide adenine dinucleotide (NAD + )-dependent enzyme, was reported to play a key role in the modulation of mitochondrial function and is considered a therapeutic target of neurodegeneration diseases [47]. It has been illustrated that SIRT3 activation presented the neuroprotective effect, reducing the beta-amyloid (Aβ) and Tau accumulation which contributed to oxidative neurotoxicity in the brain tissues of AD animals [48].…”
Section: Discussionmentioning
confidence: 99%